Pengaruh Usia terhadap Pemahaman tentang Komunikasi Kesehatan melalui TANNITO pada Petani Tomat di Desa Semangat Kabupaten Karo - annisa, Rizka; Malau, Pitto Pratiwi (Jurnal Penelitian Kesmasy, 2025)
Communication is a way for humans to interact with other living things. Communication is used to convey information, messages, and news. Usually tomato farmers communicate with each other in coffee shops at night after returning from working in the garden. So far, communication between tomato farmers has been quite good, but tomato farmers only discuss plants, the economy, harvests and pesticides. No tomato farmers communicate about health news. Thus, this study aims to increase tomato farmers' awareness of the importance of health that starts from themselves. This study uses TANNITO (Tomato Farmers' Recommendation Response) as a message to be conveyed to tomato farmers in Semangat Village, Merdeka District, Karo Regency. TANNITO is five health messages that can help tomato farmers to be aware of the dangers of pesticide exposure when working in tomato gardens. The study was conducted on 40 tomato farmers in Semangat Village, Merdeka District by looking descriptively at the influence of age on tomato farmers' understanding of the health messages conveyed in TANNITO.